Cochlear Implantation: Is Hearing Preservation Necessary in Severe to Profound Hearing Loss? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2011)
Objectives: The goal of the cochlear implant surgery is to place the electrode array with minimal damage to preserve the residual hearing. Round-window insertion can be performed in a manner that is potentially less traumatic than the standard cochleostomy. The purpose of the study was to investigate audiological results of the round-window approach using standard electrode. Methods: A retrospective study was performed to evaluate our experience in patients with implanted through round window between January 2007 and March 2009. Sixty patients had undergone cochlear implant surgery through the round window with full insertion of a standard electrode array. Preoperative and postoperative pure-tone thresholds were measured for implanted ears in the range of 250 to 4000 Hz. Results: Within these 60 cases, 31 patients had been evaluated. The population comprised 16 women and 15 men. The mean age was 15.96 years (range, 4-64 years). Follow-up times ranged from 6 to 26 months. Preservation of low-frequency hearing (250 and 500 Hz) was achieved in 27 (87%) of 31 patients. Complete hearing preservation (all frequencies) was accomplished in 11 patients (35.48%). No hearing could be determined postoperatively in 4 patients (12.9%), having preoperative thresholds of 120 dB at 250, 500, and 1000 Hz. Conclusions: Round-window approach has been widely used for preservation of residual hearing. In our patients with severe to profound hearing loss, we preserved residual hearing. Although the residual hearing cannot be sufficient for using additional acoustic stimulation, the preserved residual hearing means minimal damage and a more convenient cochlea, so this is promising for future development.
Keywords: Cochlear implantation; round-window approach; standard electrode; residual hearing; ELECTRIC-ACOUSTIC STIMULATION; AUDITORY-SYSTEM; INSERTION; DESIGN